Mycological Evaluation in oak forests in protected terrestrial landscape “Miraflor - Moropotente” the municipality of Estelí - Nicaragua (Revista Científica Estelí, 2015)
This study analyzes the patterns of diversity and distribution of macrofungi in the protected area of Miraflor – Moropotente, Esteli - Nicaragua, having as main variables the height and condition of the oak forests of the area (Quercus segoviensis and Quercus sapotaefolia), that relate to whether the described variables affect the presence or absence of macrofungi, were designated a total of 12 sampling areas and applied different diversity indices such as Shannon index, Simpson and Sorensen to value diversity alpha and beta levels. He found 31 families 55 genera grouped with 85 morphospecies, which meant a total of 1722 specimens distributed in the different sampling areas. We can say that based on the results that there is no significant difference in the diversity of macrofungi taking into account the variables described above.Keywords: Macrofungi, diversity, distribution, rates of biodiversity, conservation.